A study on trend analysis of spices export from India - KRISHNAMOORTHY, D.; RAJA S, VINITH (The journal of contemporary issues in business and government, 2020)
The research paper titled “ A study on trend analysis of spices export from India” is an attempt to predict the factors influencing the export of spices in India. In this analysis we have predicted the export quantity and value of spices for the year 2021 by using the secondary data of quantity and values for the past 5 years. Through this analysis exporters will be able to analyse the international market and predict the demand for export of spices in future.